Relationship between vitamin D status, body composition and physical exercise of adolescent girls in Beijing - Leng, Huat Foo; Q., Zhang; K., Zhu; G., Ma; A., Trube; H., Greenfield; D. R., Fraser (Springer Verlag, 2009)
Summary Little is known about the prevalence of actual vitamin D deficiency in healthy school-aged adolescents, particularly in China. The aim of this study was to examine the prevalence of hypovitaminosis D and to identify whether there was any association between vitamin D status, body composition and physical exercise in 323 Chinese adolescent girls in Beijing, China (40°N). Introduction It is well recognized that persistent severe vitamin D deficiency is associated with the bone abnormalities of rickets and osteomalacia. However, there is now evidence suggesting that low vitamin D status, not previously considered to be a state of deficiency is associated with secondary hyperparathyroidism, increased bone remodelling and other clinical signs thought only to be found in severe vitamin D deficiency. Hypovitaminosis D in healthy children and adolescents has been reported frequently in many countries, especially in winter. Methods We performed a cross-sectional analysis of 323 Chinese adolescent girls in Beijing in winter. Mean age of the subjects was 15.0 (±0.4) years. About 32.8%, 68.4% and 89.2% of the subjects were at risk of vitamin D deficiency when defined as plasma concentrations of 25(OH)D of 25, 37.5 or 50 nmol/L, respectively. Results This cross-sectional analysis of 323 Chinese adolescent girls in Beijing in winter showed that hypovitaminosis D was common in these subjects. In addition, body mass index, milk intake, participation in organized sports and total physical activity were all significant independent determinants of vitamin D status. An inverse association was found between plasma 25(OH)D and intact-parathyroid hormone (iPTH) concentration. Body mass index (BMI), milk intake, participation in organized sports and total physical activity all emerged as major independent determinants of vitamin D status as assessed by plasma 25(OH)D concentration. Vitamin D status was positively associated with lean body mass (LBM), but there was no association with the degree of body adiposity. Regardless of the concentration of 25(OH)D in blood used to define vitamin D deficiency, hypovitaminosis D was common in these subjects. Conclusion It is recommended that policies be developed to prevent vitamin D deficiency in adolescent girls. Further studies are needed to identify the mechanisms whereby vitamin D status is related to exercise and to body composition during growth.